2005
DOI: 10.1063/1.1900924
|View full text |Cite
|
Sign up to set email alerts
|

p -type conductivity in cubic (Ga,Mn)N thin films

Abstract: The electrical and magnetic properties of p-type cubic (Ga,Mn) IntroductionThe emerging field of semiconductor spintronics relies on the ability to manipulate the electron spin in a semiconductor device, thus offering new prospects for non-volatile high speed information storage and processing. An important milestone in this field was the discovery of carrier-mediated ferromagnetism in III-V compounds doped with Mn [1]. Intensive efforts have since led to ferromagnetic transition temperatures T C in excess of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
(50 reference statements)
1
23
0
Order By: Relevance
“…In addition to (Ga,Mn)As, (Zn,Mn)Te:N, and related systems, recent indications of ferromagnetism in p- (Ga,Mn)N [98,99] and p-(Ga,Mn)P [100], appear to support the conclusion about the importance of delocalized or weakly localized carriers in mediating efficient spin-spin interactions. However, in those and other experimentally relevant cases, non-uniformity associated with hole localization, and perhaps with competing ferromagnetic and antiferromagnetic interactions, is seen to affect strongly ferromagnetic properties.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to (Ga,Mn)As, (Zn,Mn)Te:N, and related systems, recent indications of ferromagnetism in p- (Ga,Mn)N [98,99] and p-(Ga,Mn)P [100], appear to support the conclusion about the importance of delocalized or weakly localized carriers in mediating efficient spin-spin interactions. However, in those and other experimentally relevant cases, non-uniformity associated with hole localization, and perhaps with competing ferromagnetic and antiferromagnetic interactions, is seen to affect strongly ferromagnetic properties.…”
Section: Discussionmentioning
confidence: 83%
“…Reports of ͑Ga,Mn͒N epilayers synthesized in cubic and hexagonal crystal structures, of p-type and n-type ferromagnetic ͑Ga,Mn͒N, and of multiple ferromagnetic phases in one material all add to the complex phenomenology of these wide-gap DMSs ͑Korotov et al, 2001;Graf et al, 2002;Graf, Gjukic, et al, 2003;Arkun et al, 2004;Edmonds, Novikov, et al, 2005;Hwang et al, 2005;Sawicki, Dietl, et al, 2005͒. Uncertainties apply also to the interpretation of ferromagnetism seen in the ͑Ga,Mn͒P samples studied to date, which have been prepared by post-MBE ion implantation of Mn followed by rapid thermal ͑Theodor-opoulou et al., 2002;Poddar et al, 2005͒ or pulse-lasermelting annealing ͑Scarpulla et al, 2005͒. Experiments in these materials have not yet established unambiguously the nature of magnetic interactions in the ͑III, Mn͒P compounds.…”
Section: B Search For High Transition Temperaturesmentioning
confidence: 99%
“…One of the approaches to eliminate these internal fields is the utilization of metastable non polar zinc-blende (zb) structures. It has also been reported that zb group IIInitrides have a quantum confined Stark effect in lowdimensional heterostructures 6 , high p-type conductivity in (Ga,Mn)N thin films 7 and negative differential resistance (NDR) at the resonant tunneling diode of the cubic Al(Ga)N/GaN 8,9 . Consequently a lot of interest is constantly attracted by this family of materials.…”
Section: Introductionmentioning
confidence: 99%